Lease expirations and CRE property performance - David P. Glancy; J. Christina Wang (Federal Reserve Bank of Boston, 2023)
This study analyzes how lease expirations affect the performance of commercial real estate (CRE) properties and how these patterns changed during the COVID-19 crisis. Even before the pandemic, lease expirations were associated with a notable increase in the downside risk to a property's occupancy or income, particularly in weaker property markets. These risks became more pronounced during the pandemic, driven mostly by office properties. During the pandemic, the adverse effect of lease expirations on office occupancy increased more than 50 percent overall, and it doubled for offices in central business districts (CBDs). This amplified effect of office lease expirations serves as a harbinger of further deterioration as leases continue to roll over in coming years, especially among CBD offices. Across lender groups, nonbank and large bank lenders are more exposed than regional and community banks to office loans in those distressed CBDs. This pattern somewhat alleviates the concern that CRE portfolio credit risk will exacerbate the headwinds faced by this latter group of banks.
Keywords: R30; R33; G21; G23; 330; Commercial real estate; lease expirations; COVID-19; office loans; bank loan exposure